INTRODUCTION OF NEW EFFECTIVE METHODS IN THE TRAINING OF NURSING STAFF IN PRIMARY HEALTH CARE INSTITUTIONS (World Bulletin of Public Health, 2022)
This article analyzes the role of PMS nurses in society, professional potential, qualification categories, social status and professional qualities. According to the study, we can conclude about the state and modern methods of training paramedical workers
Keywords: Advanced training; medical education; patronage nurse; training